METHODS OF RESTORING PARTS OF AGRICULTURAL MACHINES - Dudnikov, A. A.; Dudnikov, I. A.; Dudnyk, V. V.; Burlaka, O. A. (Scientific Progress & Innovations, 2021)
Restoration of worn parts of agricultural tillage equipment is technically and economically justified, because it can significantly reduce delay time, as well as improve the quality of repairs and positively affect the reliability of these machines. The purpose of this study is to increase the durability of the machining surface of the parts during vibration machining. The article shows the effect of friction on the deformation unevenness in the layers of deformed material. The expediency of details’ restoration of tillage machines by more effective technologies, namely plastic deformation has been substantiated. The researches have been made based on the theory of dislocations as to deformation strengthening process of the machined material of farm tillage machines’ details working in the conditions of the increased abrasive wear. The influence of dislocations on internal stresses’ formation and strengthening of the surface layer of the machined detail has been shown. It has been established that the friction that occurs during the restoration, contributes to the surface deformation in the layer of the detail deformed material. It has been determined that the friction force that appears during the machining of the restored part depends on its material. The dependence on determining the force of contact friction between the surfaces of the tool for machining and the machined detail has been given. Calculations for determining the tangential stresses affecting the contact friction surfaces have been made. The mathematical value of contact friction has been established. The values of the friction coefficient at usual and vibrational deformation of the restored part have been given. It has been determined that the smallest value of the friction coefficient is at 0.5 mm amplitude of oscillations. Also, theoretical studies have shown that at vibration machining, the friction coefficient is reduced by 2.5 times. Reducing the friction coefficient helps to strengthen the surface of the machined part.